Kilka uwag o języku liturgii - Ożóg, Kazimierz (Słowo. Studia językoznawcze, 2021)
Every human action in the dimension of the person and group is surrounded by language. The rule of being in a word also applies to religion and especially to the relationships of man and community with God. The article analyses the fundamental role of language in the liturgy of the Catholic Church. In the author’s view the great communication act defining liturgical events consists of a series of mocro-acts: worship, prayer, thanksgiving, repentance and theological statement. Liturgy is a great character behavior. The shape of liturgical formulas is logical, transparent, representing mainly the high variety of Polish.